The angular characteristics of Moon-based Earth observations. Issue 3 (3rd March 2020) - Guo, Huadong; Ren, Yuanzhen; Liu, Guang; Ye, Hanlin
ABSTRACT: The Moon, Earth's only natural satellite, is a potential new platform for Earth observation. Moreover, with the wide applicability of the angular information from remote sensing data, it has been attracting increasingly more attention. Accordingly, this study focuses on the angular characteristics of Moon-based Earth observations. Using ephemeris DE430 and Earth orientation parameters, the position and attitude of the Sun, Earth, and Moon were obtained and their coordinates normalized to a single framework using coordinate transformations between the related reference systems. Then, an angular geometric model of Moon-based Earth observations was constructed, and the corresponding angular algorithms were presented. The results revealed the angular range and distribution characteristics of Moon-based Earth observations. For every point on the surface of the Earth, the view and solar zenith angles all vary widely, which decreases with increasing latitude. The view and solar zenith angles all vary widely with the largest range of values in the equatorial and polar regions and a smaller range of values in mid-latitudes. Furthermore, the range of solar angles of Moon-based Earth observations is the same as that of all-time solar angles, indicating the potential for monitoring and understanding large-scale geoscientific phenomena using Moon-based Earth observations.